Assessment of factors influencing the process electrohydraulic water treatment - Alexander Anatolievich, Belov; Ðlexey Nikolaevich, Vasilyev; Andrey Anatolievi, Musenko (International Journal of Engineering and Technology, 2018)
The article is devoted to modeling the assessment of factors affecting the process of electrohydraulic water treatment. A screening two-level experiment according to the plan of Plackett-Berman is planned and carried out. A matrix of the Plackett-Berman plan is being developed with factors in coded units and an objective function in physical units. Significant factors that affect the process of obtaining fertilizers during electro-hydraulic treatment of solutions are identified. An error variance estimate is given. The method of random balance is used to separate non-essential variables and dominant factors that may in one way or another influence the process under study. A mathematical model is being developed, which includes 15 linear effects and 105 paired interactions. The plan matrix is determined and the random balance experiment results are identified; scatterplots are built, on the basis of the results of which significant factors are identified, whose influence on the process is eliminated. Each of the contributions is estimated based on the determination of the coefficients of the respective samples; checks the significance of the coefficients and estimates of each of the contributions by the t-test. The most significant factors are the magnitude of the applied voltage; storage capacitors; number of pulses.Â Â Â